MANAJEMEN KONSTRUKSI PADA PELAKSANAAN LANJUTAN GEDUNG STADION INDOOR KABUPATEN LANDAK KALIMANTAN BARAT - Syahbani, Gusti; Utomo, satriyo; reski, indah anjar (Jurusan Teknik Sipil Polnep, 2022)
Construction management consultant is the management of construction project management withlarge-scale projects. Analysis of the implementation of construction management can be applied to projectimplementation to manage, organize, and find solutions, including the timing of the project implementation.Good timing and management is one of the success factors of a construction construction project, managingproject management and implementing construction management in large-scale projects. Setting and managingtime with the aim of minimizing and reducing risks that may occur in an Indoor Stadium building project inLandak Regency. The time risk that may occur is the delay in project completion.Precise, fast, and safe timing are very helpful in completing the work on the Indoor Stadium buildingconstruction project in Landak Regency. Good time management is the process of planning, organizing, andcontrolling project execution. So that the timeliness at each stage of the work must be in accordance with theplanned time. Determination, management, and planning. Meanwhile, the extension of time is based on thingsthat have been coordinated with all parties and can be accounted for.The purpose of this final project is to identify the various factors involved in the presence of aconstruction management consultant at each stage of the project. This requires proper time management ateach stage of the work, so that the work is completed as expected. The implementation of this Final Projectincludes: literature review, determination of required data, secondary data, and data analysis as well asconclusions drawn from the analysis of the application of time management in construction projects and thisFinal Project is carried out at the Indoor Stadium in Landak Regency.Keywords: Cost Management, Human Resource Management, Time Management, Quality Management, WorkSafety Management